Changes in Verbal Fluency in Parkinson's Disease - Rosenthal, Liana S. (Mov Disord Clin Pract, 2016)
BACKGROUND: The test for semantic verbal fluency is quick and easy to administer. Decreases in semantic verbal fluency would suggest executive dysfunction among individuals with Parkinson's disease (PD). METHODS: The National Parkinson Foundation's Outcomes Project is a multicenter study that seeks to determine best practices in PD management. We analyzed data from the baseline and two annual follow‐up visits to determine the annual rate of verbal fluency change and determinants of that change. Linear mixed modeling was used to assess relationships between verbal fluency, clinical characteristics, quality of life, and caregiver burden. RESULTS: There were 1,322 participants with an average age of 67.3 years, of whom 37% were women. Mean baseline verbal fluency scores at baseline were 18.81 (standard deviation = 6.25). Verbal fluency scores did not change among patients who were at our cohort's average age and average PD duration (8.4 years) and who had no other associated conditions (beta = −0.02; P = 0.80). Verbal fluency, however, did decrease for individuals with PD duration greater than the average (beta = −0.25; P = 0.03), age greater than the average (beta = −0.022; P < 0.01), a Hoehn and Yahr >=3 (beta = −0.31; P = 0.04), and in those with cardiovascular disease (beta = −0.32; P = 0.01) or psychiatric symptomatology (beta = −0.34; P = 0.01). Individuals with higher verbal fluency scores had better quality of life (P < 0.01) and decreased caregiver burden (P < 0.01). CONCLUSIONS: Clinicians should monitor verbal fluency scores to evaluate cognitive decline among individuals with PD. Modifiable risk factors for verbal fluency changes include psychiatric symptomatology and cardiovascular disease. Clinicians may use verbal fluency testing to identify individuals at risk for decreased quality of life and increased caregiver burden, allowing for focused interventions.